DEMONSTRATION SITE STATION (DSS) SEBAGAI WAHANA PEMBERDAYAAN KEPEDULIAN MASYARAKAT TERHADAP KUALITAS SUNGAI CISADANE - Sri Unon Purwati (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2009)
Efforts for increasing Cisadane water quality is an important steps for maintaining Cisadane water quality fordrinking water purposes. Cisadane water quality of monitoring result from 2003-2007 should be used as a backgroundfor increasing water quality efforts. The result of monitoring should be utilized for the efforts increasingCisadane water quality and should be socialized to community surrounding nearly the river. The DemonstrationSite Station (DSS) is a vehicle of community development behavior should be developed for coping domesticwaste problems. The DSS is form that area environment friendly and as a pioneer creating environment friendlysociety at Cisadane River vicinity